Double Coronary Aneurisms in Kawasaki Disease Successfully Treated with Anakinra: A Case Report - K, Bouayed; S, Lotfi; A, Sakhi (Archives of Clinical and Medical Case Reports, 2022)
Background: Kawasaki disease is an acute inflammatory vasculitis of the medium and small-caliber arteries, usually occurring in children under 5 years of age. It is known to cause coronary aneurysms, which are more frequent in refractory forms. While the treatment of classical Kawasaki disease is well codified, the treatment of refractory forms remains nonstandardized. Anakinra, an interleukin-1 receptor antagonist, appears to be a promising therapeutic alternative. Case Presentation: We report a case of 9 months old girl, diagnosed with Kawasaki disease, non-responsive to two doses of intravenous immunoglobulins and acetyl salicylic acid, who developed aneurysms, successfully treated with Anakinra 3 months with 5 years of follow-up. Conclusions: Our experience highlights Interleukin-1 blockade effectiveness in reducing Kawasaki disease systemic inflammation. We believe that our case adds more evidences to the potential role of interleukin-1 receptor antagonist as second or third-line therapy in some cases of refractory Kawasaki disease, particularly with severe involvement of coronary arteries.